The Influence Of Participative Leadership And Flexible Work Environment On Product Innovation With The Mediation Of Work Motivation - Deri Prayudi; Hari Setia Putra; Nur Faliza (Management Studies and Entrepreneurship Journal (MSEJ), 2023)
This research investigates the intricate relationships among participative leadership, flexible work environments, work motivation, and product innovation within the organizational context of PT As Putra Group. Utilizing a quantitative approach and employing random sampling, the study examines the impact of participative leadership on work motivation and subsequent product innovation. Additionally, it explores the influence of a flexible work environment on both work motivation and product innovation. The findings reveal a highly significant relationship between participative leadership and product innovation, emphasizing the pivotal role of leadership styles in shaping innovative capabilities. Furthermore, the study identifies a significant relationship between a flexible work environment and product innovation, indicating the importance of adaptable work structures in fostering innovative outcomes. These insights contribute to the understanding of organizational behavior and innovation, offering practical implications for leaders aiming to enhance both employee motivation and product innovation. The research underscores the interconnected nature of leadership, work environments, and motivation in shaping a culture of continuous improvement and creativity within contemporary workplaces like PT As Putra Group.